Rancang Bangun Penangkap Embun Untuk Meningkatkan Efisiensi Aplikasi Pengabut Air Sebagai Model Mitigasi Urban Heat Island Masa Depan: Design And Construction Of Dew Catchers To Increase The Efficiency Of Water Sharing Applications As A Future Urban Heat Island Mitigation Model - Andreas Luis; Daniel Wolo; Insar Damopolii (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
This research was conducted to develop a dew-catching vehicle that will be used to support the application of a water misting system. The dew catcher design is expected to overcome the problem of too large a mist grain diameter in low-pressure water misting applications. The study was conducted using a 110 psi pressure pump and ten nozzles measuring 0.3 mm that sprayed mist from a height of 2 M. In this study, and the dew catcher design used can overcome the disturbance of water droplets due to the production of too large mist grains at low pressure misting. The maximum temperature drop that can be achieved is 7.6°C.